Social Media Addiction and Time Management Skills of University Students in Akwa Ibom State, Nigeria - Ugochukwu, Ezeonwumelu, Victor; Nneka, Nwikpo, Mary; Okoro, C.C.; Idara, Ekanem, Eyaema (Global Journal of Social Sciences Studies, 2021)
The study was conducted to ascertain the influence of social media addiction on time management skills of university students in Uyo Senatorial District. The population of the study comprised all the second year 2018/2019 students in the University of Uyo. This consisted of a total of 5854 students. The simple random sampling technique was used to select 650 students from the 13 Faculties in the University of Uyo. Two instruments - Social Media Addiction Scale and Time Management Inventory - were adopted for the study and piloted on 80 year two students in the institution. The pilot test yielded a Chronbach alpha reliability coefficient of .78 which was deemed appropriate for the study. The data generated were analyzed using Mean and Standard deviation, while the hypotheses formulated were tested using the t-test statistics. The findings revealed that Facebook and Twitter addiction had significant influence on students’ time management skills. Instagram addiction, however, was not found to have significant influence on students’ time management skills. The recommendations made were that social networking sites should develop features that would help integrate learning contents into social media platforms and that virtual learning should be explored to enhance student engagement, among others.